DA EDUCAÇÃO COMO DIREITO AO DIREITO À EDUCAÇÃO: A NÃO REGULAMENTAÇÃO E A IMPROVISAÇÃO COMO PRÁTICA AUTORITÁRIA DA POLÍTICA EDUCACIONAL NO MUNÍCIPIO DE CHOPINZINHO/PR (2007-2015) - Coppe, Marta Regina (2018)
The present dissertation has as object of study the Pedagogical Proposal for the initial years of the nine years elementary education from 2007 of the municipality of Chopinzinho / PR and the respective Municipal Plan of Education of 2015. Initially, we also wanted to analyze the municipal curricular guidelines, but, in the course of the research, we verified that they were not elaborated by the municipality, leaving only the Pedagogical Proposal and the Municipal Education Plan. Faced with this, the initial question was: What educational policy is expressed in the pedagogical proposal for the initial years of the nine years elementary education of the municipality of Chopinzinho / PR and in the Municipal Plan of Education? That said, the objective was to analyze both documents, trying to detect the educational perspective and the policy contained therein, considering their liberal or critical position, thus positioning the discussion about education as a right and the right to education within the municipal context. The selected research techniques were bibliographic review, questionnaire application and documentary analysis. In addition to the analysis of works by reference authors on the subject of research, relevant documents, including legislative documents were analyzed, such as the Federal Constitution of 1988, the LDBEN of 1996, the National Curricular Guidelines for Elementary Education of 1998, the National Education Directives Basic Guidelines for 2010, the National Curricular Guidelines for Elementary Education of nine years of 2010, in addition to the Curricular Guidelines for Basic Education in the State of Paraná, 2008. This selection was made concomitant with the research objective, as well as the National Plans of Education of the Decades 2014-2024 and the State Plan of Education of 2015. The analysis starts from the assumptions of dialectical historical materialism with emphasis on the categories of totality, mediation and contradiction. Through the study, it was verified that authoritarianism, together with the deregulation of rights and the denial of access to education as a fundamental right, materialized in the municipality as an extension of hegemonic politics at the national level. There remains the need to discuss the construction of curricular guidelines, based on education as a right, in the municipality of Chopinzinho, thus overcoming the minimalist view of the right to education, since the analyzes showed that both documents - Pedagogical Proposal for years of elementary education and the Municipal Plan of Education - represent a policy that only induces the legality of actions, giving the subjects only what the legislation guarantees, contrary to what is expected in an emancipatory perspective of education, which is the guarantee of the needs of citizens.